Intellectual Capital, Islamicity Performance Index, dan Kinerja Keuangan Bank Syariah di Indonesia (Studi Pada Tahun 2015-2020) - CAHYA, BAYU TRI; Sari, Dita Apriliana; Paramitasari, Ratih; Hanifah, Umi (IAIN Kudus, 2021)
This study aims to determine intellectual capital, Islamicity performance index, and financial performance on Islamic banks in Indonesia for 2015-2020. Islamicity performance index was proxied by a profit-sharing ratio, zakat performance ratio, and Islamic income vs. non-Islamic income, and financial performance was proxied by return on asset (ROA). This study uses causal associative research using a quantitative approach. The population of this study was all Islamic commercial banks in Indonesia for the 2015-2020 period, with a sample of 7 banks. Sampling was done by the purposive sampling method. Data collection uses secondary data, namely the documentation technique, by taking the annual report of each Islamic commercial bank in Indonesia for the 2015-2020 period. Data analysis technique using multiple linear regression analysis. The results of this study indicate that intellectual capital has a positive and significant effect on return on asset (ROA), profit sharing ratio has a significant negative effect on return on asset (ROA), zakat performance ratio has a positive and significant effect on return on asset (ROA), and Islamic income vs. non-Islamic income has a positive and significant effect on return on asset (ROA).Keywords: Intellectual Capital; Profit Sharing Ratio; Zakat Performance Ratio Islamic Income vs Non-Islamic Income; and Financial Performance.